Early Lung Cancer Detection - Inage, Terunaga; Nakajima, Takahiro; Yoshino, Ichiro; Yasufuku, Kazuhiro (Clinics in chest medicine, 2018)
Lung cancer is the most common cause of cancer deaths worldwide. A major reason for poor prognosis is that patients are usually diagnosed at an advanced stage and thus there are limited options for curative treatment at the time of diagnosis. Early detection may improve lung cancer survival, as demonstrated in computed tomography screening studies. New and innovative bronchoscopic methods have been developed for the early diagnosis of lung cancer. High-precision bronchoscopic imaging technology, such as optical biopsy, may potentially replace traditional biopsy techniques. This article reviews the advanced technologies for detection of early lung cancer.